High-Flow Nasal Cannula Therapy in Children With Acute Respiratory Distress With Hypoxia in A Pediatric Intensive Care Unit–A Single Center Experience - Chang, Chih-Ching; Lin, Yi-Chen; Chen, Tzu-Chun; Lin, Jainn-Jim; Hsia, Shao-Hsuan; Chan, Oi-Wa; Lee, En-Pei (Frontiers in Pediatrics, 2021)
Aim High-flow nasal cannulas (HFNCs) show potential in the application of positive pressure, improving gas exchange and decreasing work of breathing in patients with acute respiratory distress. The aims of this study were to elucidate the indications for HFNC therapy in children of all ages and diagnoses, and to evaluate the efficacy and risk factors for failure of HFNC therapy in children with acute respiratory distress with hypoxia in a pediatric intensive care unit. Methods We conducted this retrospective cohort study at a tertiary pediatric intensive care unit between January 1, 2018 and December 31, 2020. All children, from 1 month to 18 years of age, with acute respiratory distress with hypoxia and HFNC therapy were eligible. The clinical data were reviewed. Results One hundred and two children met the eligibility criteria for the study, of whom 57 (55.9%) were male, and the mean age was 7.00+/-6.79 years. Seventy-eight (76.5%) of the children had underlying disorders. The most common indications for the use of HFNC therapy were pneumonia (40, 39.2%), sepsis-related respiratory distress (17, 16.7%) and bronchiolitis (16, 15.7%). The failure rate was 15.7% (16 of 102 children). Higher initial and maximum fraction of inspiration O2 levels and lower initial and lowest SpO2/FiO2 (S/F) ratio were early and possible signs of failure requiring escalation of respiratory support. Conclusion In our population, we found that HFNC therapy could be initiated as the first-line therapy for various etiologies of acute respiratory distress with hypoxia in a pediatric intensive care unit and for all age groups.